(Making Bamboo Charcoal And Bamboo Vinegar With Phyrolization Process) - H G Pohan; M Maman Rohaman (Warta Industri Hasil Pertanian, 2008)
To increase value added of bamboo, research of making charcoal and bamboo vinegar have been conducted by using of phyrolization process of varieties bamboo. The study was aimed to determine characteristics of phyrolization, charcoal and bamboo vinegar. The research result show that the phyrilization temperature for bamboo andong and  petung was between 650-680